The Challenge of a Global Sociological Imagination - Caselli, Marco (Italian Sociological Review, 2022)
Many sociologists suggested that – due to globalization processes – we must go beyond methodological nationalism in studying societies. But how is this possible? We still miss a convincing answer. In order to find it, we need a “global sociological imagination”. C.W. Mills wrote that sociological imagination is “the vivid awareness of the relationship between experience and the wider society”. Starting from this, global sociological imagination should be the vivid awareness of the relationships between personal experience, local dynamics, multi-local dynamics, global dynamics and processes. Going further, sociology studies (social) facts but, contrary to popular belief, facts don’t speak for themselves. So, we need sociological imagination, and now global sociological imagination, in order to understand these facts. We also know that sociology is looking for good answers but, before this, sociology needs good questions. So, we need global sociological imagination also to find good questions about our global society.